Translational diagnostic neuroimaging in mild traumatic brain injury and multiple sclerosis - Allen, Christopher Martin (2024)
Translation of promising neuroimaging technologies into diagnostic tests requires diagnostic test accuracy studies. This thesis describes two such studies, MEGAbIT and DECISIve. As well as assessing analytical performance, this thesis will attempt to determine the effects of these new technologies on patients and the wider healthcare system.